Hot crimping through innovative inductive heating in the production of electric motors - Kühl, Alexander; Zitzelsberger, Maximilian; Seefried, Johannes; Masuch, Michael; Miller, Tim; Franke, Jörg (2019 IEEE International Electric Machines and Drives Conference, IEMDC 2019, 2019)
In electrical machine production, the coil ends of the winding must be electrical contacted in the correct phase. The hot-crimping process is a commonly used method for joining the enameled copper wires to a cable lug in one process step. However, due to its working principle, this technology has the strong disadvantage of high tool wear, which leads to frequent maintenance. In this paper, an improved hot crimping method is presented to overcome this detriment. Therefore, inductive heating is used to strip the wires and the tools for crimping are made of a nonconductive technical ceramic.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Contacting; Electric drives production; Hot crimping; Inductive stripping; Winding